The "S\~ao Paulo Mystery": The role of the criminal organization PCC in reducing the homicide in 2000s - Marcelo Justus; Daniel Cerqueira; Tulio Kahn; Gustavo Carvalho Moreira (EconomiA, 2018)
We move forward in identifying the causes of the marked and systematic reduction in the homicide rate in S\~ao Paulo state in the 2000s. Its main objective was that of investigating the role of the criminal organization PCC in this process. We constructed a first-difference fixed effects model with a spatial structure where we controlled for various socioeconomic and demographic measures and for the presence of firearms and law-enforcement, among other measures. Our results do not support the PCC hypothesis at the level of the state of S\~ao Paulo.
Keywords: K42; 330; Criminal organization; Homicide; Violence